Techno-environmental evaluation of liquefied natural gas fuelled combined gas turbine with steam cycles for large container ship propulsion systems - Alzayedi, Abdulaziz M. T.; Sampath, Suresh; Pilidis, Pericles (MDPI, 2022)
Restrictions on emissions are being imposed by regional and international shipping organisations, which raise the question of which marine fuel and technology can most effectively replace heavy fuel oil and diesel engines. The aim of this study is to find appropriate advanced combined gas and steam turbine cycles for marine propulsion systems in a large container ship with respect to the evolving maritime environmental regulations. The selection criteria are the thermodynamic performance, emissions, size, and weight of advanced combined gas and steam turbine cycles in a large container ship. Two baselines are used: a diesel engine using marine diesel oil and a combined gas and steam turbine system using liquefied natural gas and marine diesel oil. Then, liquefied natural gas cycles are examined based on fuel replacement and enhanced to assess the benefits of liquefied natural gas over marine diesel oil. The results show that the enhanced liquefied natural gas combined gas and steam turbine cycles are the most efficient, at up to 1.6% higher than the other cycles. Regarding the size and weight, the combined gas and steam turbine propulsion system is approximately 24.7% lighter than the original diesel engine propulsion system.
Keywords: advanced combined gas and steam turbine cycle; techno-environmental; combined gas and steam turbine cycle; large container; ship; propulsion systems; liquefied natural gas; marine diesel oil; nitrogen oxide; carbon dioxide